1993
DOI: 10.2466/pr0.1993.73.1.79
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Homeschooling in Kansas

Abstract: Personal interviews with a nonrandom sample of four current or former homeschooling mothers indicated that these mothers were homeschooling to avoid what they perceived as negative social or academic aspects of public schools and to promote closer family interaction. While the families appeared to be divided along traditional gender-role assignments, fathers were responsible for at least one of the children's subjects, usually science, religion, or physical education. While all the mothers saw time management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(30 citation statements)
references
References 4 publications
0
29
1
Order By: Relevance
“…The apparent disparity between absolute and pre-synaptic zinc levels stems from the fact that about 80% of total zinc in brain is not amenable to histochemical detection (Cole et al, 1999). This “invisible” pool of zinc is found in all six classes of enzymes and in intracellular receptors, where it is normally coordinated by four to six ligands, frequently supplied by histidine and cysteine, in conserved binding motifs (Vallee and Falchuk, 1993; Auld, 2001). …”
Section: Initial Identification Of Vesicular Zinc In Synaptic Terminamentioning
confidence: 99%
See 1 more Smart Citation
“…The apparent disparity between absolute and pre-synaptic zinc levels stems from the fact that about 80% of total zinc in brain is not amenable to histochemical detection (Cole et al, 1999). This “invisible” pool of zinc is found in all six classes of enzymes and in intracellular receptors, where it is normally coordinated by four to six ligands, frequently supplied by histidine and cysteine, in conserved binding motifs (Vallee and Falchuk, 1993; Auld, 2001). …”
Section: Initial Identification Of Vesicular Zinc In Synaptic Terminamentioning
confidence: 99%
“…A number of reports have demonstrated behavioral alterations in animals fed a zinc-restricted diet for several weeks, including increased anxiety or depression, and impaired spatial memory and extinction learning (Keller et al, 2000; Takeda et al, 2007; Tassabehji et al, 2008; Whittle et al, 2010). One caveat with dietary zinc deficiency models is that they can lead to multisystemic dysfunction, particularly in peripheral tissues with rapid turnover, and compromise many zinc-dependent reactions (Vallee and Falchuk, 1993). In the hippocampus, zinc deficiency has been shown to reduce the total number of synaptic vesicles in boutons (Lu et al, 2000).…”
Section: Synaptic Zinc and Memorymentioning
confidence: 99%
“…Zinc deficiency is a worldwide health problem, and it is estimated that at least 25% of the population is at risk [6]. Low zinc can cause pleiotropic problems, such as abnormal morphogenesis, growth retardation, and dysfunction of the reproductive and immune systems [2,7-11]. Too much zinc accumulation is also harmful to cells and organisms.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that over 90% of this trace element present in erythrocytes is bound with carbonic anhydrase and superoxide dismutase [12]. Furthermore, zinc mobilises vitamin A, a potent antioxidant, from the liver, thus maintaining its proper levels in the blood [11].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc is crucial for the proper functioning of approximately 300 hormones and enzymes in the human body [11, 12], the latter representing all the classes taking part in the synthesis and degradation of proteins, carbohydrates, fats and nucleic acids. Zinc constitutes a structural element of alkaline phosphatase (ALP), with four of its atoms being present in the enzyme.…”
Section: Introductionmentioning
confidence: 99%